Wearable brain computer interface (BCI) system - Lum, Jabez Hong Bang (2016)
In recent years, there is an increased interest in the field of Brain Computer Interface (BCI). BCI allows translation of human brain activity into operational signals. On the other hand, Hybrid Brain Computer Interface is a combination of two or more BCI systems working hand in hand with various brain wave patterns in order to increase the availability of applications and enhance the accuracy of interpreting brain activity. One of the application of BCI is BCI X-Ray Trainer, exploiting Electroencephalography (EEG), using mainly Alpha and Gamma waves that will allow live-feed monitoring through a Muse Headband. These signals that are captured will go through a processing system that is specially programmed for visual studio application, allowing user to remotely operate a conveyor belt with the aids of prior training video game. In this project, it will be addressing Hybrid BCI Pulse Sensor and BCI X-Ray Trainer which aims to locate an ideal location on the forehead that will provide the best heart rate signal in reference to the conventional finger feedback site. Moreover, improving the concentration level of X-Ray luggage inspectors while examining their state of emotions.